Response of Pineapple Callus (Ananas comosus Merr.) through In-Vitro Colchicines Treatment - Nurul Istiqomah; Muh. Shofi (Scientiae Educatia: Jurnal Pendidikan Sains, 2018)
Pineapple Plant (Ananas comosus (L.) Merr) is a fruit plant that has a high economic value. Increased variety of pineapple preparations lead to increased demand for pineapple fruit. Polyploidation is one way to increase the varieties using colchicine. This study aims to know the pineapple explants of callus response after being treated by colchicine using in vitro method. This research used Group Randomized Design (GRD) which variations concentration of Colchicine 0%, 0.01%, 0.05%, and 0.1%. Parameters were observed to response and thickness of callus of pineapple explants. Data were analyzed using F test and DMRT test in which significance level of 5% with SPSS 17 program. The results showed that pineapple plant explant able to respond colchicine concentration marked with thicker callus. The best colchicine treatment to induce pineapple explants callus was concentration 0.1% of colchicine.